Influence of glycation of plasma proteins in diabetes on the binding interaction with polyphenols - Xu, Wei; Chen, Longsheng; Shao, Rong (Current drug metabolism, 2014)
Diabetes mellitus is one of the most serious diseases in the world. The degree of glycated plasma proteins is increased in diabetics compared to non-diabetic subjects. This mini-review focuses on the influence of glycation of human serum albumin (HSA) in diabetes on the binding interaction with dietary polyphenols. The non-enzymatic glycation of HSA leads to a conformational change in HSA, which in turn influences the ligand binding properties. HSA glycation is believed to reduce the binding affinities for acidic drugs such as dietary polyphenols and phenolic acids.